The symbolic meaning of Malay Sambas marriage pantuns: Islam, love, and culture - Adhadika, Febi; Mariyadi (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2025)
Pantun has symbols that represent the culture of the Malay community, including in pantun meminang. Therefore, the purpose of this study is to reveal the symbolic meaning of Malay Sambas pantun meminang in relation to Islamic symbols, love, and culture. This study employs a descriptive qualitative research method with a semiotic approach. Data for this study were collected through interviews with four respondents from the Sambas Malay community who are familiar with marriage pantuns. Based on the analysis results, it can be seen that there are symbolic meanings that indicate Islamic symbols, love, and culture in the pantuns. The findings regarding Islamic symbols include mentioning the name of Allah and greetings. Findings related to the symbol of love include expressions of love and the strengthening of relationships, while findings related to culture include the culture of maintaining relationships and the culture of proposing marriage. This study successfully revealed these three symbols comprehensively, unlike previous studies that addressed them separately, making it a valuable reference for relevant institutions in conducting in-depth interpretations of pantun, particularly pantun meminang.